Feasibility of patient-focused behavioral interventions to support adults experiencing chronic noncancer pain during opioid tapering: a systematic literature review. Issue 8 (2nd March 2021) - White, Ruth; Bruggink, Laura; Hayes, Chris; Boyes, Allison; Paul, Chris
Abstract: Guidelines for chronic noncancer pain prioritize behavioral treatments. In clinical practice transition from opioids to behavioral treatments is often not endorsed by patients or providers. Feasible interventions to support opioid tapering are needed, particularly in primary care. The objectives of this paper is to review the feasibility of behavioral interventions to support opioid tapering. Electronic databases (MEDLINE, Embase, PsycINFO, and CINAHL) were searched from inception to June 2019 to identify original studies reporting feasibility (consent rates; completion rates; patient-reported acceptability; integration into clinical practice; and adverse events) of opioid tapering and transition to behavioral treatments for adults experiencing chronic noncancer pain. Google scholar and contents tables of key journals were also searched. Two authors independently extracted data and assessed methodological quality using The Quality Assessment Tool for Quantitative Studies. Eleven publications met inclusion criteria, of which three were conducted in primary care. Consent rates ranged from 27% to 98% and completion rates from 6.6% to 100%. Four studies rated at least one component of patient acceptability: helpfulness from 50%–81%; satisfaction 71%–94%, and "recommend to others" 74%–91%. Three studies reported provider perspectives and two studies reported adverse events. Quality assessment indicated all 11 studies were moderate or weak, primarily due to selection bias and lack of assessor blinding. There was also considerable heterogeneity in study design. The limited available data suggest that attempts to translate opioid tapering interventions into practice are likely to encounter substantial feasibility challenges. One possible way to ameliorate this challenge may be a clear policy context, which facilitates and support opioid reduction. Abstract : People experiencing chronic non-cancer pain and reliant on opioids report variable willingness to taper. Patients find supportive behavioural treatments helpful during opioid reduction.